Diagnóstico de las condiciones institucionales para una educación inclusiva en la Escuela Superior Politécnica Agropecuaria De Manabí Manuel Félix López - Bravo Escobar, Antony Alexander (2021)
The main objective of the research work was to diagnose the institutional conditions for inclusive education in the Escuela Superior Politécnica Agropecuaria de Manabí "Manuel Félix López", work that began with the compilation of information on the main topics such as institutional conditions, inclusive education and the diversity of disabilities in the institution; Methodologies were applied, such as the inductive and deductive method that allowed the extraction of theoretical information and also allowed to know directly the real events in the same way to analyze each one of them, in this way the technique of interviewing the person in charge of the Vice-Rectorate Area of Extension and Student Well-being, which set out its criteria for the protocol to be followed through rules, regulations and curricular adaptation guide for students with disabilities or different abilities, among the various questions that stand out, on the other hand, a survey assigned to students was conducted to Identify the lack of technological equipment and the institutional conditions of the university and verify if the teachers are able to teach classes towards these students with special educational needs, after these results an improvement plan was made to eliminate deficiencies that affect the students and strengthen education inc lusive quality within the university.